Endothelial glycocalyx in acute care surgery - what anaesthesiologists need to know for clinical practice - Astapenko, David; Benes, Jan; Pouska, Jiri; Lehmann, Christian; Islam, Sufia; Cerny, Vladimir (BMC anesthesiology, 2019)
The endothelial glycocalyx (EG) is the thin sugar-based lining on the apical surface of endothelial cells. It has been linked to the physiological functioning of the microcirculation and has been found to be damaged in critical illness and after acute care surgery. This review aims to describe the role of EG in severely injured patients undergoing surgery, discuss specific situations (e.G. major trauma, hemorrhagic shock, trauma induced coagulopathy) as well as specific interventions commonly applied in these patients (e.g. fluid therapy, transfusion) and specific drugs related to perioperative medicine with regard to their impact on EG.EG in acute care surgery is exposed to damage due to tissue trauma, inflammation, oxidative stress and inadequate fluid therapy. Even though some interventions (transfusion of plasma, human serum albumin, hydrocortisone, sevoflurane) are described as potentially EG protective there is still no specific treatment for EG protection and recovery in clinical medicine.The most important principle to be adopted in routine clinical practice at present is to acknowledge the fragile structure of the EG and avoid further damage which is potentially related to worsened clinical outcome.
Keywords: Humans; perioperační péče; Fluid therapy; Anaesthesia; Perioperative Care; Endothelial glycocalyx; lidé; anesteziologie; glykokalyx; mikrocirkulace; Glycocalyx; Acute care surgery; Surgical Procedures, Operative; Endothelial Cells; chirurgie operační; Anesthesiology; Major trauma; endoteliální buňky; Transfusion; Microcirculation